Development of a curriculum in molecular diagnostics, genomics and personalized medicine for dermatology trainees. (22nd July 2016) - Murphy, Michael J.; Shahriari, Neda; Payette, Michael; Mnayer, Laila; Elaba, Zendee
Abstract : Background: Results of molecular studies are redefining the diagnosis and management of a wide range of skin disorders. Dermatology training programs maintain a relative gap in relevant teaching. Objective: To develop a curriculum in molecular diagnostics, genomics and personalized medicine for dermatology trainees at our institution. The aim is to provide trainees with a specialty‐appropriate, working knowledge in clinical molecular dermatology. Methods: The Departments of Dermatology and Pathology and Laboratory Medicine collaborated on the design and implementation of educational objectives and teaching modalities for the new curriculum. Results: A multidisciplinary curriculum was developed. It comprises: (i) assigned reading from the medical literature and reference textbook; (ii) review of teaching sets; (iii) two 1 hour lectures; (iv) trainee presentations; (v) 1‐week rotation in a clinical molecular pathology and cytogenetics laboratory; and (vi) assessments and feedback. Residents who participated in the curriculum to date have found the experience to be of value. Conclusions: Our curriculum provides a framework for other dermatology residency programs to develop their own specific approach to molecular diagnostics education. Such training will provide a foundation for lifelong learning as molecular testing evolves and becomes integral to the practice of dermatology.